ANALISIS KADAR NITRIT (NO2-) DAN AMONIA (NH4+) PADA INSTALASI PENGOLAHAN AIR MINUM DENGAN METODE SPEKTROFOTOMETRI UV-Vis - Salsabillah, Rizka Dely; Rusmaniar, Rusmaniar (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2023)
Water is a necessity that is needed by living things, especially humans in carrying out daily activities such as washing, bathing and cooking. The chemical parameters required for drinking water are aluminum, iron, hardness, chloride, manganese, pH, zinc, sulfate, copper, ammonia, and nitrites. Nitrite is partially oxidized nitrogen which lasts only temporarily and exists in the oxidation process between nitrite and ammonia. Ammonia is an indicator of air pollution. This study aims to determine the levels of nitrite and ammonia contained in water. From this study, the results of the analysis of nitrite levels contained in raw water were 0.6 mg/l, filtered water was 0.5 mg/l, and clean water was 0.4 mg/l. the level of ammonia contained in clean water is 0.009 ppm. The nitrite content contained in PDAM water meets the quality of Permenkes No. 492/MENKES/PER/2010, namely the maximum level allowed is 1 mg/L. And the level of ammonia contained in clean water does not exceed the threshold of PERMENKES No.492/MENKES/PER/ IV/2010, which states that the maximum limit for ammonia levels in clean water is 1.5 ppm